Effects of a synthetic PEG-ylated Tie-2 agonist peptide on endotoxemic lung injury and mortality - David, Sascha; Ghosh, Chandra C; Kümpers, Philipp; Shushakova, Nelli; Van Slyke, Paul; Khankin, Eliyahu V; Karumanchi, S Ananth; Dumont, Dan; Parikh, Samir M (American journal of physiology. Lung cellular and molecular physiology, 2011)
A synthetic 7-mer, HHHRHSF, was recently identified by screening a phage display library for binding to the Tie-2 receptor. A polyethylene-oxide clustered version of this peptide, termed vasculotide (VT), was reported to activate Tie-2 and promote angiogenesis in a mouse model of diabetic ulcer. We hypothesized that VT administration would defend endothelial barrier function against sepsis-associated mediators of permeability, prevent lung vascular leakage arising in endotoxemia, and improve mortality in endotoxemic mice. In confluent human microvascular endothelial cells, VT prevented endotoxin-induced (lipopolysaccharides, LPS O111:B4) gap formation, loss of monolayer resistance, and translocation of labeled albumin. In 8-wk-old male C57Bl6/J mice given a ∼70% lethal dose of endotoxin (15 mg/kg ip), VT prevented lung vascular leakage and reversed the attenuation of lung vascular endothelial cadherin induced by endotoxemia. These protective effects of VT were associated with activation of Tie-2 and its downstream mediator, Akt. Echocardiographic studies showed only a nonsignificant trend toward improved myocardial performance associated with VT. Finally, we evaluated survival in this mouse model. Pretreatment with VT improved survival by 41.4% (n = 15/group, P = 0.02) and post-LPS administration of VT improved survival by 33.3% (n = 15/group, P = 0.051). VT-mediated protection from LPS lethality was lost in Tie-2 heterozygous mice, in agreement with VT's proposed receptor specificity. We conclude that this synthetic Tie-2 agonist, completely unrelated to endogenous Tie-2 ligands, is sufficient to activate the receptor and its downstream pathways in vivo and that the Tie-2 receptor may be an important target for therapeutic evaluation in conditions of pathological vascular leakage.